204 Rosewood Lane [compact disc, unabridged] - Macomber, Debbie (Macomber, Debbie. Cedar Cove series., 2008)
Grace, a seemingly reserved librarian, shows the town of Cedar Cove what she is truly made of when her husband mysteriously vanishes, forcing her to call upon her inner strength and courage to help her two daughters deal with his disappearance.